Lyric X-Marks: Genre and Self-Determination in the Harp Poems of John Rollin Ridge. (27th August 2018) - Carr, Ryan
Abstract: Although John Rollin Ridge (Yellow Bird) is best known today as the author of the first novel by a Native American, he may also have been the first Native writer to publish lyric poetry. This essay considers two poems written by Ridge on the theme of "my harp, " and explores the implications of identifying these two poems as lyrics. Recent work in historical poetics has called into question the motives and methods by which literary scholars identify nineteenth-century poems as lyrics. Taking on board many of the concerns of New Lyric Studies, this essay suggests that it still makes sense to read Ridge's harp poems as lyrics since that genre's abstract and self-estranging mode of address suited the various situations of exile in which he found himself following Cherokee removal: first, as an adolescent living and studying in Arkansas and plotting revenge for the murder of his father; and, later, as a gold prospector and newspaper editor in California, where Ridge had fled after killing another Cherokee as part of the same factional struggle within which his father was murdered. Amid all the upheavals of his life, writing lyric poetry served Ridge as a way of asserting a persistent identity as a writer of poems whose readership was always uncertain——as what he called "a stranger in a stranger land."